2016
DOI: 10.1038/ncomms12593
|View full text |Cite
|
Sign up to set email alerts
|

Metal-responsive promoter DNA compaction by the ferric uptake regulator

Abstract: Short-range DNA looping has been proposed to affect promoter activity in many bacterial species and operator configurations, but only few examples have been experimentally investigated in molecular detail. Here we present evidence for a metal-responsive DNA condensation mechanism controlled by the Helicobacter pylori ferric uptake regulator (Fur), an orthologue of the widespread Fur family of prokaryotic metal-dependent regulators. H. pylori Fur represses the transcription of the essential arsRS acid acclimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 52 publications
1
39
0
1
Order By: Relevance
“…This lack of repression could be a consequence of the impact of nickel on the cytosolic pH ( Fig. 1, Right) or the influence of HpNikR on HpArsR activity, and highlights the integrated nature of the regulatory networks in this organism (13,42). Finally, transcription of the cahA gene and levels of the ComH protein have been reported to be acid-responsive (39,43), but under these conditions no impact of acid shock was detected in the wild-type cells and acid-dependent repression of cahA was observed in the ΔnikR knockout strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of repression could be a consequence of the impact of nickel on the cytosolic pH ( Fig. 1, Right) or the influence of HpNikR on HpArsR activity, and highlights the integrated nature of the regulatory networks in this organism (13,42). Finally, transcription of the cahA gene and levels of the ComH protein have been reported to be acid-responsive (39,43), but under these conditions no impact of acid shock was detected in the wild-type cells and acid-dependent repression of cahA was observed in the ΔnikR knockout strain.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, arsR and amiE are repressed by HpFur in an irondependent manner (42,54), and ureA, ureG, amiE, and amiF are coactivated by HpArsR (23,46). Furthermore, arsR is regulated through a complex mechanism involving HpNikR, HpFur, and HpArsR itself, suggesting that the expression of arsR is sensitive to the various stimuli that influence the activities of all three transcription factors (42). These overlapping regulons complicate the interpretation of the global expression data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this may be true for complex promoters, e.g. the arsR promoter were the interaction of Fur and NikR governs a sofisticated signal integration logic52, this possibility does not explain the role of intracistronic binding sites. Tentatively, intragenically bound NikR could hint at nucleoid-associated functions important for chromosome organization53.…”
Section: Discussionmentioning
confidence: 96%
“…NikR is also a positive transcriptional regulator of ArsRS involved in acid adaptation. Roncarati et al 12 reported a metal-responsive promoter DNA compaction mechanism, which modulates the transcriptional regulation and coordinated response to environmental stimuli. In the presence of nickel, NikR antagonizes the Fur-mediated regulation and DNA compaction at the ArsRS promoter.…”
Section: Nickel Is Essential For Gastric Colonization By H Pylorimentioning
confidence: 99%